Literature Review Asuhan Keperawatan Lansia pada Pasien Penderita Gout Arthritis - Dwi Nurfajriyah; Airin Putri Aprilia; Elsyana Fadhilah; B. Tamas Arbania Efendi; Armatella Makdalena; Sri Ariyanti (Jurnal Kajian dan Penelitian Umum, 2025)
Background: Elderly (elderly) is not a disease but a life process characterized by a decrease in the body's ability. The elderly will continue to experience the aging process, causing some functions and metabolism in the body to decrease. One metabolic disorder that is often experienced by the elderly is Gout Arthritis or gout. Gouty arthritis or gout is usually characterized by acute joint inflammation caused by the formation of crystallized uric acid. This gouty arthritis disease arises because of consuming too much food and drinks containing purines, including tea, coffee, offal (tripe, spleen, intestines and so on), if you consume more food containing purines, the level of gout in the body will be high. Increased production is caused by consuming foods with high purine levels. In addition, due to drugs, obesity, hypertension, hyperlipidemia, and diabetes mellitus.The purpose of this literature review: To carry out nursing care with the problem of gouty arthritis in the Elderly.Research Methods: The search for article data sources was carried out through an inclusion study design using Literature Review.Results: Analysis of journal reviews there are differences in the level of effectiveness between ergonomic exercises (70%) and warm compresses (30%) where ergonomic exercises are more influential than warm compresses in reducing the pressure of uric acid levels.Conclusion: There is an effect of ergonomic exercise on reducing uric acid levels in patients with gouty arthritis.